Current trends of HIV/AIDS in Asia (South East Asia Journal of Public Health, 2018)
It is very important to recognize the trends in HIV/AIDS in specific areas such as Asia because it is vital to understanding the effectiveness of current approaches towards diagnosis and treatment. It is also very important to understand the risk factors that greatly predispose people in Asia to contracting HIV/AIDS such as lifestyle, culture, and religion. This review extensively analyzes the current trends of HIV/AIDS in India, China, Thailand, Cambodia and Indonesia. Additionally, cultural diversity carries certain social and religious stigmas associated with the disease. These social stigmas also pose as a significant influence on government involvement with regards to the funding of HIV/AIDS awareness, education, prevention, and the protection of human rights. Lack of education about the methods that help people from the disease and mode of transmission remains a significant hindrance in the prevention of a further rise in epidemiological statistics. Moreover, these factors are attributed to the rising incidence or risk of HIV within several populations amongst these countries. This review also analyzes the clinical presentation, epidemiological statistics, and the financial and socioeconomic impacts of HIV/AIDS in India, China, Thailand, Cambodia and Indonesia. Financial burdens and lack of government infrastructure in the healthcare systems are largely responsible for the rapidly rising prevalence of the disease among these populations, along with the inaccessibility to prevention and treatment methods. Furthermore, the scarcity of available antiretroviral and preventative medications is discussed. Lastly, this review explores various methods of diagnosis, treatment and prevention plans that are implemented in modern medicine with respect to HIV/AIDS.South East Asia Journal of Public Health Vol.7(2) 2017: 3-11